Baby Loves Lunar Phases on Chinese New Year! - Spiro, Ruth; Chan, Irene (Illustrator) (Watertown : Charlesbridge, 2021)
"While celebrating Chinese New Year, Baby discovers the science behind the lunar calendar and the phases of the moon"--.
new kids book 2022 fall.
Ages 0-3
Keywords: Lunar calendars -- Juvenile literature; Moon -- Phases -- Juvenile literature; Chinese New Year -- Juvenile literature